2011
DOI: 10.1073/pnas.1017385108
|View full text |Cite
|
Sign up to set email alerts
|

Interleukin 6 signaling promotes anti-aquaporin 4 autoantibody production from plasmablasts in neuromyelitis optica

Abstract: Neuromyelitis optica (NMO) is an inflammatory disease affecting the optic nerve and spinal cord, in which autoantibodies against aquaporin 4 (AQP4) water channel protein probably play a pathogenic role. Here we show that a B-cell subpopulation, exhibiting the CD19 int CD27 high CD38 high CD180 − phenotype, is selectively increased in the peripheral blood of NMO patients and that anti-AQP4 antibodies (AQP4-Abs) are mainly produced by these cells in the blood of these patients. These B cells showed the morpholog… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

8
311
3
7

Year Published

2012
2012
2018
2018

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 402 publications
(329 citation statements)
references
References 46 publications
8
311
3
7
Order By: Relevance
“…We used Ig transcriptome and Ig proteome analyses to evaluate the clonal relationship between different peripheral B‐cell populations and AQP4‐specific B cells in the CSF of active seropositive NMO patients. In contrast to prior studies,16, 17 we identified clonal relationships between CSF B cells and circulating class‐switched memory, DN memory, and plasmablast populations. We also observed an overlap between CSF B cells and memory B cells and plasmablasts from the spleen of one patient.…”
Section: Discussioncontrasting
confidence: 98%
See 2 more Smart Citations
“…We used Ig transcriptome and Ig proteome analyses to evaluate the clonal relationship between different peripheral B‐cell populations and AQP4‐specific B cells in the CSF of active seropositive NMO patients. In contrast to prior studies,16, 17 we identified clonal relationships between CSF B cells and circulating class‐switched memory, DN memory, and plasmablast populations. We also observed an overlap between CSF B cells and memory B cells and plasmablasts from the spleen of one patient.…”
Section: Discussioncontrasting
confidence: 98%
“…Interestingly, a high degree of connectivity was observed between ASCs and activated naïve B cells in active systemic lupus erythematosus patients 12. Our data suggest that naïve B cells may also be actively recruited into the enhanced ASC response associated with NMOSD clinical relapse 16. As circulating IgG is the product of long‐lived bone marrow‐resident plasma cells, these newly emerging AQP4‐specific B‐cell clones likely contribute little to the serum AQP4‐IgG that passively crosses the blood–brain barrier during relapse.…”
Section: Discussionmentioning
confidence: 63%
See 1 more Smart Citation
“…The NR1‐IgG were unlikely to have arisen from pre‐existing circulating ASCs derived ex vivo, given that they were not generated under conditions known to maintain ASCs in culture (IL‐6 ± BAFF) 16. By contrast, under conditions known to proliferate circulating B cells (including IL‐2 and R848),10 NR1‐IgG was consistently detected in culture supernatants both with and without CD40‐ligand (Fig 3).…”
Section: Resultsmentioning
confidence: 96%
“…Recently, tocilizumab has been used to treat neuromyelitis optica (NMO) [9], an autoimmune CNS disease with pathogenic antiaquaporin-4 autoantibodies, although the immunopathogenesis of NMO is complex with pathological evidence of autoantibody, complement, T cells, B cells, neutrophils, and eosinophils [10]. IL-6 is elevated in NMO attacks, is involved in autoantibody production, and is used as a disease biomarker [11]. By contrast, the literature regarding IL-6 in AE is small and only now emerging, although some small studies have shown that IL-6 is elevated in AE [12,13].…”
mentioning
confidence: 99%